The Journey-Inter Continental Concerts - Mosallaeipour, Sam; Mohseni Zonoozi, Shahed (http://intercontinentalconcerts.org/, 2016)
The First music album booklet of Inter Continental Concerts
Keywords: Inter Continental Concerts; The Journey